Language acquisition and development in children with cochlear implant - Alves, Helena (2014)
Objective: Check the vocabulary acquisition in children with cochlear implants, depending on their hearing age. Materials and Methods: This study analyzed 100 Inventories (Inventory on the Development of Communication - MCDI - WS) completed by parents of children implanted at the Department of Otorhinolaryngology, CHUC, EPE - CHC. The MCDI - WS is an inventory that seeks to check language acquisition between 16 and 30 months of age. The analyzed inventories were divided into 4 groups according to the hearing age of the child. The group data were analyzed and compared. Results: The children who produced more words were the ones who had used the implant for a longer period of time. The was a increasing vocabulary proportional to the auditory age. Conclusion: The results show that there is an increase in vocabulary with increasing the listening experience of the child and consequent exposure to oral verbal language.